Замок у с. Кривче як пам’ятка архітектури Західного Поділля - Пришляк, О.Б. (Сіверщина в історії України, 2021)
Стаття присвячена будівництву, архітектурним дослідженням,
вивченню історичних хронологічних процесів оборонного замку в селі
Кривче – архітектурної спадщини Західного Поділля як важливого
історичного регіону України; опрацьовано проєкти пристосування
та використання як об’єкта культурної спадщини Національного
заповідника «Замки Тернопілля». Збережені залишки пам’ятки архітектури державного значення – замку в селі Кривче Борщівського
району – є важливим об’єктом для дослідження оборонної архітектури XVII століття і розвитку туризму в цій місцевості. The article is devoted to the process of construction and architectural research,
the study of historical chronological processes of the defensive castle in the village
of Kryvche – the architectural heritage of Western Podillya as an important historical
region of Ukraine; Projects of adaptation and use as a cultural heritage site of
the National Reserve «Ternopil Castles» have been developed. Preserved remains
of an architectural monument of national importance - the castle in the village of
Kryvche Borshchiv district is an important object for the study of defense architecture
of the XVII century and the development of tourism in this area.
The castle is located on a high hill bounded on the south side by the rocky
banks of the Tsyganka River and on the north side by a deep ravine, and is part of
the fortifications of the Kamyanets-Podilsky Fortress, with which it may have been
connected by underground passages.
Kryvchensky Castle in the 17th century was one of the best defensive castles in
Western Podillya - it had a developed system of dry defensive ditches on three sides
– western, southern and eastern. On the north side, the steep slope of the natural
hill on which the castle is located, made it difficult to approach it.
Currently, the castle is preserved in fragments. Only two hexagonal towers
remind of the former castle at the entire original height to the level of cornices –
south-east and south-west, and the defensive wall between them is partially preserved
to the level of the 2nd tier of towers at a height of 4 meters
The study of individual castles of Podillya gives grounds to suggest that in the
XVII century. the art of fortification was not inferior to the European, developing
in the stream of the latest achievements of military experience. Therefore, the
question arises of further research of the architectural monument of fortification
defense - the castle in Kryvche.